Fishery Management Complexes: An Impediment or Aid to Sustainable Harvest? A Discussion Based on the Northeast Skate Complex. (29th March 2013) - Hogan, Fiona; Cadrin, Steve; Haygood, Alyssa
Abstract: There are seven species of skates (family Rajidae) found along the East Coast of the USA. All seven species are currently managed by the New England Fisheries Management Council as a single management complex extending from the Gulf of Maine to Cape Hatteras. The objective of the management plan is to ensure the long‐term sustainability of fishing for each species via a trip limit approach. Two species are harvested in two distinct commercial fisheries. Northeast Fisheries Science Center trawl survey data and published literature were examined to investigate differences between the individual species in the skate complex. Each species exhibited a unique thermal and geographic range in addition to vital life history traits (e.g., age at maturity, longevity, and maximum size). Thorny Skate Amblyraja radiata and Smooth Skate Malacoraja senta have narrow thermal ranges and maintain a more northern distribution. Barndoor Skate Dipturus laevis have a moderate thermal habitat. Little Skate Leucoraja erinacea and Winter Skate L. ocellata have broad thermal ranges and are distributed throughout the management area. Limited inferences can be made about the thermal preferences of Clearnose Skate Raja eglanteria without data from south of Cape Hatteras, but they appear to have a broad thermal range within the management area. Rosette Skate L. garmani have a narrow thermal range and tend to be found in the deep offshore mid‐Atlantic region. The validity of managing multiple distinct species in a complex is questioned. This example shows that a mixed‐stock management strategy may be inadequate to meet the sustainability needs of each species and the associated fisheries. A management strategy focused on individual species may lead to a more efficient harvest of targeted species while allowing for the rebuilding of overfished species. Received November 8, 2011; accepted December 27, 2012